THEATER PR: PR STRATEGY IN THE MODERN THEATER ENVIRONMENT - Serhii Vazhynskyi (Інтегровані комунікації)
The article explores the importance and relevance of PR strategies in the contemporary theater environment. It examines the approaches and tools theaters can use to attract, retain, and engage with audiences in an era of rapidly changing technologies and cultural trends. The article reveals the importance of analyzing the need to understand the target audience and studying its expectations for further developing individual strategies.